Makassar city of South Sulawesi Province has potency and opportunity to develop fisheries industry to become the biggest fisheries industry in the eastern Indonesian region. Geographically, the Makassar city is located in a strategic eastern Indonesian region that bringing consequency to become the gate of export for trading product. The research objectives are to create development model of fisheries industry in Makassar city base on the fishing port, to describe the existing condition of fis - Danial .; John Haluan; Mustaruddin .; Darmawan . (Forum Pasca Sarjana, 2011)
Makassar city of South Sulawesi Province has potency and opportunity to develop fisheries industry to become the biggest fisheries industry in the eastern Indonesian region. Geographically, the Makassar city is located in a strategic eastern Indonesian region that bringing consequency to become the gate of export for trading product. The research objectives are to create development model of fisheries industry in Makassar city base on the fishing port, to describe the existing condition of fishing activities and its influence level to formulate significant influence factors, and to formulate development strategy of fisheries industry in Makassar city. This research was conducted from March to November 2009 in Makassar city. Data was taken from fishery industries as respondent, such as fishing characteristic, fishing industry, management industry, export, and policy. The result of SEM analysis showed the goodness of fit index criterias, namely: chi-square, probability, RMSEA, CFI, IFI, GFI, AGFI, and PGFI. Based on the regression analysis on weight values of the interaction with other factors, it can be significant or non-significant relation, wherereas the significant relation is necessary. The goverment policy on the development of Untia Archipelago Fishing Port in Makassar city is to continue fishing activity to provide materials of fishery industry. Developing model of fisheries industry base on the fishing port with eight factors can be used to plan the fishery industry development. Key words: model, fishing port, fishery industry, SEM